Rancang Bangun Alat Pembakaran Minim Asap Pada Tungku Arang Dengan Sistem Konsentrasi Asap - Didy Suharlan; Deni Syahreiza Siagian; M. Nuh Hudawi Pasaribu (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
This design aims to design a smoke-less combustion device in a charcoal stove with a smoke concentration system which is expected to minimize the smoke generated from burning coconut shell charcoal. The design implementation was carried out in the workshop of the Mechanical Engineering Study Program, Maintenance and Repair of the Tanjungbalai Polytechnic. This tool has two tubes, the inner tube is in the form of a cylinder, the overall height is 930 mm, and the diameter is 480 mm with a reactor tube capacity of 17 liters, the coconut shell is 25 kg. The outer tube is cylindrical in shape, has a height of 1200 mm and a diameter of 560 mm. This heat conducting pipe is made of stainless which is inside the 2nd tube or inner tube, this pipe has a height of 380 mm and a width of 60 mm in diameter. This pipe also has 12 holes and 1 hole at the top.